Estimativas de parâmetros genéticos de características reprodutivas de ovinos Santa Inês utilizando inferência Bayesiana - Montalván, Zoila Catalina Rabanal de (2013)
The objective of this study was to estimate the values of the (co)variance components and genetic parameters for reproductive traits in Santa Inês sheep raised in different states and registered with the Associação Sergipana dos Criadores de Caprinos e Ovinos (Goat and Sheep Breeders Association of Sergipe). The database used was provided by the Association and comprised pedigree observations originating from 11,483 registered individuals, out of which 2,238 were born in the program and had calving records, being part of the relationship matrix. After restriction application, there remained 843 animals for analysis which had data related to the age at first calving (IPP1), 151 with data related to the median calving interval (IPM2), and 151 to the interval between first and second calvings (IPS3). To obtain the values of (co)variance components and genetic parameters, we used the Bayesian inference under an animal model with the Gibbs sampling algorithm aided by the MTGSAM program. The two-trait linear model used considered the contemporary group as the fixed effect for IPP1, IPM2, and IPS3, and the type of calving and the age of the animal at calving as the covariate effect. The estimated values of h2 for IPP1, IPM2, and IPS3 were equal to 0.19 ± 0.0459, 0.0169 ± 0:36, and 0:35 ± 0.016 respectively. The estimated heritability for IPP1is considered average and the values for IPM2 and IPS3 were considered high, which leads to the conclusion that these characteristics can be used as selection criteria in a breeding program of Santa Inês sheep. The estimated value for the correlation between IPP1 and IPM2, and IPP1 and IP2, were negative and equal to rg12 = -0.2569 ± 0.0546, rg13= -0.1134 ± 0.0553, which were physiological expected low values that represent a trend which suggests individual selection for those traits. However, the rg23 shows a positive and high trend of 0.9601 ± 0.0091 for IPM2 and IPS3 suggesting indirect selection as the best option for these traits.